Comprehensive Physical Characterization of Silver Nanoparticles: Multimodal Evaluation of Material Properties - Suri Sahil; Ghosal Shreya; Upadhyay Viyat Varun; Kansal Lavish; Dhyani Manoj; Lakshmi A. Anitha; Kumar Raman; Fallah Mohammed H. (E3S Web of Conferences)
This study investigates the characterization of silver nanoparticles (AgNPs) through a variety of analytical techniques to evaluate their physical properties and potential applications. Particle size analysis, utilizing Dynamic Light Scattering (DLS), Transmission Electron Microscopy (TEM), and Scanning Electron Microscopy (SEM), consistently showed an average diameter of approximately 20-30 nanometers. Surface area assessments, conducted via BET analysis and gas adsorption, revealed a surface area ranging from 32 to 48 m²/g, indicating the nanoparticles’ applicability across various fields. Composition analysis using Energy-Dispersive X-ray Spectroscopy (EDX), X-ray Diffraction (XRD), and Atomic Force Microscopy (AFM) confirmed that the AgNPs comprised 84-94% silver content, supporting their crystalline structure. Optical properties evaluated through UV-Vis spectroscopy demonstrated stable absorption peaks between 410 and 440 nanometers, with plasmon resonance values from 2.82 to 3.24 electron volts (eV). Despite slight variations in light reflectivity, the uniform optical characteristics across samples suggest consistent behavior. Overall, this comprehensive characterization enhances the understanding of AgNPs, underscoring their potential in nanotechnology, biomedicine, and environmental applications.